Assessment of the Risk of Musculoskeletal Disorders in the Upper-limb in Greenhouse Workers by the OCRA and ACGIH-HAL Methods - Varmazyar 1, Sakineh; Choubdar 1*, Mohadese (Shahroud Journal of Medical Sciences, 2018)
Background: Greenhouse workers are exposed to a variety of biomechanical risks, repetitive movements, and awkward posture. This study aimed to assess the risk of upper limb injuries in greenhouse workers and its relationship with musculoskeletal disorders (MSDs).Methods: This descriptive, analytic, cross-sectional study was conducted among 50 greenhouse workers. The data related to MSDs were collected using a body map and interview. The OCRA and ACGIHHAL methods were used to assess the risk factors of the upper limb disorders in six repetitive tasks. The data were analyzed by univariate logistic regression.Results: The results showed that 62% of the workers had MSDs in the upper limbs over the last year. Grafting task had the highest OCRA index and HAL-TLV (8.3 and 0.59). The highest percentage of pain was in the fingers (75%). Univariate regression test showed a significant relationship between the three parts of the upper limb (wrist, palm, and fingers) and the OCRA index (OR=0.30, 95%CI=0.15-0.61; OR=0.26, 95%CI=0.11–0.59; OR=0.21, 95%CI=0.08–0.51; respectively).Conclusions: The prevalence of MSDs was one-third in the wrist. Grafting task was the most dangerous activity, and tasks such as pruning, weeding, and transplanting had a medium risk. Use of ergonomic tools in tasks such as grafting, pruning, and harvesting is recommended. In weeding task, in which repetitive work is done for a long time, management measures such as training, job rotation, and increasing rest time could reduce MSDs.